Environmental impact assessment of cement considering environmental impact allocation of blast furnace slag in Japan - Nakamura Ryonosuke; Ogawa Yuko; Kawai Kenji (MATEC Web of Conferences)
The cement industry emits a significant amount of CO2, but utilizes a large volume of waste and by-products from other industries in Japan. However, few studies have comprehensively evaluated both the environmental burden from CO2 emissions and the environmental impact reduction by resource recycling. The environmental burdens often are not allocated to by-products such as blast furnace slag and fly ash, potentially leading to an overestimation of the environmental impacts of cement, especially blended cement. This study aims to assess how environmental burden allocation to by-products affects environmental impact evaluations of related industries and various types of cement. The study focuses on cement production, steelmaking, and coal-fired power generation in Japan, with a further subdivision of steelmaking processes. The environmental burdens related to by-products were allocated to them based on weight and cost. LIME3, a life cycle impact analysis method developed in Japan, was used to calculate the environmental impacts. The results of the environmental impact assessment of Portland cement and blended cement showed that Portland cement has a greater reduction in environmental impacts than blended cement in terms of no allocation, allocation by weight, and allocation by cost.